Detection of Listeria spp. and Listeria monocytogenes from small animals, soil and water samples in sarawak - Hu, Li Tze (Universiti Malaysia Sarawak (UNIMAS), 2013)
Listeria monocytogenes (L. monocytogenes) is a pathogenic Gram positive bacterium which causes a type of disease called listeriosis in humans. The common sources of infection by L. monocytogenes can be from anima'ls, contaminated water as well as undercooked food. The main objective of this research was to determine the presence of L. monocytogenes in small mammals, soil and water samples from the selected sites in Sarawak namely Sebangkoi Recreational Park (Sarikei), Matang Kubah National Park (Kuching) and Bako National Park (Kuching). The samples collected were enriched in Tryptone Soy Broth (TSB) while P ALCAM agar was used for the selective isolation of Listeria spp. Upon growth on PALCAM agar, Listeria spp. produced colonies which were greyish green with black halo. The presence of L. monocytogenes was further confirmed with Polymerase chain reaction (PCR) to identify the virulence-associated gene in this pathogen. The hlyA virulence gene in L. monoc;ytogenes codes for a specific enzyme called listeriolysin 0 (LLO) which lyses macrophages by the secretion of pore-forming toxin. Overall, 38.6% of the isolates obtained from the samples at the three selected sites in Sarawak contained Listeria spp. However, L. monocytogenes was not detected from any of the samples examined. Therefore, the wildlife hosts from the three selected sites are free from the pathogen L. monocytogenes.